2022
DOI: 10.3389/fcell.2022.874840
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology in the Comorbidities of Ehlers Danlos Syndrome

Abstract: Ehlers-Danlos Syndromes (EDSs) are a group of connective tissue disorders, characterized by skin stretchability, joint hypermobility and instability. Mechanically, various tissues from EDS patients exhibit lowered elastic modulus and lowered ultimate strength. This change in mechanics has been associated with EDS symptoms. However, recent evidence points toward a possibility that the comorbidities of EDS could be also associated with reduced tissue stiffness. In this review, we focus on mast cell activation sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The frequency of all types of Ehlers–Danlos syndrome has been estimated to be at a minimum of 1 in 5000 individuals. Among EDS patients, the hypermobility type is believed to account for up to 80–90% of all EDS patients [ 95 , 96 ]. In this subtype, patients experience hypermobile and unstable joints, along with other signs of weakened connective tissues.…”
Section: Ehlers–danlos Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of all types of Ehlers–Danlos syndrome has been estimated to be at a minimum of 1 in 5000 individuals. Among EDS patients, the hypermobility type is believed to account for up to 80–90% of all EDS patients [ 95 , 96 ]. In this subtype, patients experience hypermobile and unstable joints, along with other signs of weakened connective tissues.…”
Section: Ehlers–danlos Syndromementioning
confidence: 99%
“…Therefore, symptoms may include flushing, pruritus, urticaria, angioedema, nasal congestion, nasal pruritus, wheezing, throat swelling, headache, diarrhea, abdominal cramping, unexplained arrhythmias, and hypotensive episodes [ 95 , 98 ]. Some studies reported that up to 25% of patients with hEDS also have MCAS [ 96 ]; however, such associations raise several concerns [ 95 ]. In order to understand the attributed links between MC and EDS, it is worth familiarizing oneself with the information that has made researchers lean towards such hypotheses.…”
Section: Ehlers–danlos Syndromementioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 3 Additional consideration must also be given to the comorbidities that exist alongside the main condition due to its multisystemic nature. These include Postural Tachycardia Syndrome (PoTS), 4 Mast Cell Activation Syndrome (MCAS), 5 gastrointestinal issues, and bladder and bowel problems. 6 These comorbidities can play an important role when it comes to rehabilitation planning.…”
Section: Introductionmentioning
confidence: 99%
“…Additional consideration must also be given to the comorbidities that exist alongside the main condition due to its multisystemic nature. These include Postural Tachycardia Syndrome (PoTS) [4], Mast Cell Activation Syndrome (MCAS) [5], gastrointestinal issues and bladder and bowel problems [6]. These comorbidities can play an important role when it comes to rehabilitation planning [7].…”
Section: Introductionmentioning
confidence: 99%